The role of extension services for the successful introduction of new Musa cultivars in southeastern Nigeria - Akele, S.E.; Isirimah, N.; Brisibe, A.A.; Ortíz, R. (2000)
Black sigatoka (Mycosphaerella fijiensis) causes yield losses of 30 to 50% in banana and plantain. The cultivation of resistant cultivars is the most appropriate intervention to control this fungal leaf spot disease in Africa. The short-term approach of the International Institute of Tropical Agriculture (IITA) to control black sigatoka in Nigeria was to identify, multiply and distribute resistant cooking bananas. The Green River Project (GRP), in collaboration with IITA, has been promoting cooking bananas as a substitute for plantain in southeastern Nigeria. Five rural areas in the northern part of Rivers State (Omoku/Kreigani, Obrikom-Obie-Obor-Ebeghoro, Ebocha, Mgbede/Aggah and Okwuzi) are served by GRP. An extension officer and a rural assistant officer are responsible for transferring new techniques and cultivars to the farming community. Local farmers are regularly informed, through practical demonstrations, how to improve their current cultural practices and how to incorporate new products into their diets. Since local consumers were not accustomed to cooking bananas, the extension officers carried out palatability tests to show how this new product may be cooked and eaten. Farmers and consumers indicated that cooking bananas had smaller and softer fruits, longer cooking time and lower starch than plantains. Nonetheless, farmers are gradually accepting cooking bananas as substitute of plantain because of their resistance to black sigatoka. Hence, GRP has multiplication plots for further distribution of cooking banana suckers to farmers. The success for adoption of cooking bananas by the farming community in southeastern Nigeria will depend on creating public awareness and encouraging the planting of black sigatoka resistant cooking bananas among local farmers. This will need adequate extension services which should provide planting materials with high health status and proper technology for storage and enhanced utilization of cooking bananas after harvest. This experience with cooking bananas may provide means for a successful and fast distribution to the Nigerian farmers of new plantain or banana hybrid cultivars when they become available.